A robust approach towards sequential data modeling and its application in automatic gesture recognition - Kosmopoulos, Dimitrios I.; Varvarigou, Theodora; Chatzis, Sotirios P. (My University, 2008)
Hidden Markov models using finite Gaussian mixture models as their hidden state distributions have been applied in modeling of time series that result from various noisy signals. Nevertheless, Gaussian mixture models are well-known to be highly intolerant to the presence of outliers within the fitting sets used for their estimation. Finite Student's-t mixture models have recently emerged as a heaviertailed, robust alternative to Gaussian mixture models, overcoming these hurdles. To exploit those merits of Student's-t mixture models, we introduce in this paper a novel hidden Markov chain model where the hidden state distributions are considered to be finite mixtures of multivariate Student's-t densities and we derive an algorithm for the model parameters estimation under a maximum likelihood framework. We apply this novel approach in automatic gesture recognition and we show that our model provides a substantial improvement in data representation performance and computational efficiency over the standard Gaussian model
Keywords: Acoustics; Speech; Gaussian distribution; Markov processes; Robustness; Signal processing; Mixtures